Investigation on the turning of wire and arc direct energy deposition austenitic stainless steel - Gustavo QUADRA VIEIRA DOS SANTOS; Youhei KUJIRAI; Jun’ichi KANEKO; Takeyuki ABE (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2025)
This paper focuses on the study of the turning of Austenitic Stainless Steel products manufactured with the Wire and arc direct energy deposition (DED-Arc) process by comparing the cutting process of two different samples, one manufactured with the DED-Arc methodology and the other by the hot rolling technique, for both oblique and orthogonal cutting. Focusing on the cutting forces aspect of the cutting procedure and the chip formation, these parameters were compared for both samples. Their differences are highlighted and discussed, mainly regarding their microstructure and possible influence on turning. Although the hot rolled samples presented higher values for the cutting forces for both cases, the profile of forces was stable as was the chip formed. The DED-Arc sample, on the other hand, presented not only a high degree of variability of cutting forces but also a periodic pattern of this kind of variation. Also, non-uniform was the chips formed and their evacuation. Those changes were discussed and explained to be mainly influenced by the dendritic microstructure and the anisotropic behavior of the DED-Arc SUS316L.